Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1039/d0sc00219d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ABn-type colloidal molecules by polymerization-induced particle-assembly (PIPA)

Abstract: Using isotropic diblock copolymer spheres, polymerization-induced particle-assembly directly produces colloidal molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…In 2020, Yuan, Yang and co-workers demonstrated the preparation of rarely achieved colloidal molecules (CMs) by seeded dispersion polymerization of HPMA with PDMA- b -PBzMA nanoparticles as seeds. 33 First, the PDMA- b -PBzMA colloidal atoms (CAs) were synthesized via PISA in ethanol, it was then dialyzed against water (pH ∼ 2) to remove ethanol. In the growth of the third block, they found that phase separation between PHPMA and PBzMA occurs as the DP of PHPMA increases.…”
Section: Controlled and High-order Morphologies By Pisamentioning
confidence: 99%
“…In 2020, Yuan, Yang and co-workers demonstrated the preparation of rarely achieved colloidal molecules (CMs) by seeded dispersion polymerization of HPMA with PDMA- b -PBzMA nanoparticles as seeds. 33 First, the PDMA- b -PBzMA colloidal atoms (CAs) were synthesized via PISA in ethanol, it was then dialyzed against water (pH ∼ 2) to remove ethanol. In the growth of the third block, they found that phase separation between PHPMA and PBzMA occurs as the DP of PHPMA increases.…”
Section: Controlled and High-order Morphologies By Pisamentioning
confidence: 99%
“…The fusion and assembly of particles is an emerging method to fabricate nanomaterials with precisely controlled anisotropy or highly ordered structures 29 33 . For instance, Yuan and coworkers fabricated AB n -type colloidal particles by polymerization-induced particle-assembly using a linear ABC triblock terpolymer, and the number of n could be controlled between 2 and 6 by tuning the volume ratio of different blocks 29 . O’Reilly et al investigated the polymerization-induced fusion behaviors of polymersomes 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al. [ 19 ] also obtained higher‐order structures using polymerization‐induced particle self‐assembly (PIPA). In our system, as the C segment grows, the generated micelles started to aggregate and formed an MCM (structure (e) in Scheme 3) at 22 DPs of PGMA (C segment) (monomer conversion = 26%).…”
Section: Resultsmentioning
confidence: 99%
“…[ 3,6,17 ] PISA has also been used for synthesizing ABC terpolymer‐based higher‐order self‐assemblies such as multicompartment micelles. [ 17–20 ]…”
Section: Introductionmentioning
confidence: 99%